2013
DOI: 10.1002/adma.201204624
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Rod‐Shaped DNA‐Stabilized Silver Nanocluster Emitters

Abstract: Fluorescent DNA-stabilized silver nanoclusters contain both cationic and neutral silver atoms. The absorbance spectra of compositionally pure solutions follow the trend expected for rod-shaped silver clusters, consistent with the polarized emission measured from individual nanoclusters. The data suggest a rod-like assembly of silver atoms, with silver cations mediating attachment to the bases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
416
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(435 citation statements)
references
References 57 publications
17
416
2
Order By: Relevance
“…Since it is more difficult to produce single crystals with DNA, mass spectrometry is a more widely used tool. In a recent report, Gwinn and co-workers screened 80 DNA sequences and used multiple stages of HPLC to purify products that are stable for the HPLC process [79]. With extensive mass spectrometry and simulation work, the authors concluded that DNA stabilized AgNCs contain roughly the same amounts of neutral silver atom and silver cation.…”
Section: Characterization Of Ncsmentioning
confidence: 99%
“…Since it is more difficult to produce single crystals with DNA, mass spectrometry is a more widely used tool. In a recent report, Gwinn and co-workers screened 80 DNA sequences and used multiple stages of HPLC to purify products that are stable for the HPLC process [79]. With extensive mass spectrometry and simulation work, the authors concluded that DNA stabilized AgNCs contain roughly the same amounts of neutral silver atom and silver cation.…”
Section: Characterization Of Ncsmentioning
confidence: 99%
“…The spectra showed the distinct Gaussian shape associated with AgNC emission. [ 14,25,27,31 ] Each spectrum was fi tted to a Gaussian function to determine the emission maximum. A histogram of the average emission maxima of all the single molecules is shown in Figure 2 d along with the emission spectrum of the bulk sample.…”
Section: Single Molecule Measurements: Emission Spectra Versus Decay mentioning
confidence: 99%
“…In this case, we focus on the nearinfrared emitters using 633 nm as the excitation wavelength. Although a number of single molecule studies have been performed on AgNC to investigate specifi c photophysical parameters, [ 5,6,8,10,14,25,[27][28][29][30][31][32][33] we simultaneously measure several photophysical properties for each individual cluster, including decay times, emission spectra, and antibunching. This allows us to compare and correlate these photophysical properties within a sample to better understand the photophysical behavior and heterogeneity of these complex as-synthesized AgNC samples.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different DNA sequences produce various emission colors [1][2][3][4][5][6], allowing multiplexed detection. The emission color is likely to relate to the arrangement of silver species and their interaction with the surrounding nucleotides [6].…”
Section: Introductionmentioning
confidence: 99%